2021
DOI: 10.1177/1744806921997654
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture may alleviate neuropathic pain via suppressing P2X7R expression

Abstract: Neuropathic pain is a severe problem that is difficult to treat clinically. Reducing abnormal remodeling of dendritic spines/synapses and increasing the anti-inflammatory effects in the spinal cord dorsal horn are potential methods to treat this disease. Previous studies have reported that electroacupuncture (EA) could increase the pain threshold after peripheral nerve injury. However, the underlying mechanism is unclear. P2X7 receptors (P2X7R) mediate the activation of microglia and participate in the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…The purinergic receptors P2X4 and P2X7 are overexpressed on the cell surface of spinal dorsal horn microglia involved in microglial activation, which significantly contributes to the inflammation after SCI ( Deng et al, 2018 ; Du et al, 2019 ; Kobayakawa et al, 2019 ; Song et al, 2022 ). Electroacupuncture can inhibit P2X7 receptor-mediated microglial activation and attenuate neuropathic pain ( Wu et al, 2021a ). It can also relieve pain hypersensitivity by inhibiting P2X7 receptor-positive microglia after chronic constriction injury ( Xu et al, 2016 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…The purinergic receptors P2X4 and P2X7 are overexpressed on the cell surface of spinal dorsal horn microglia involved in microglial activation, which significantly contributes to the inflammation after SCI ( Deng et al, 2018 ; Du et al, 2019 ; Kobayakawa et al, 2019 ; Song et al, 2022 ). Electroacupuncture can inhibit P2X7 receptor-mediated microglial activation and attenuate neuropathic pain ( Wu et al, 2021a ). It can also relieve pain hypersensitivity by inhibiting P2X7 receptor-positive microglia after chronic constriction injury ( Xu et al, 2016 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…Studies have shown that the EA at ST36 and BL60 in SNL and DNP models can reduce P2X3 receptors in L4–6 DRGs ( 37 , 43 , 44 , 46 ). EA also reduces P2X4 ( 36 , 45 ) and P2X7 receptors ( 38 ) in L4–6 DRGs, inhibits excitatory postsynaptic potentials, neural loops excitability from the periphery to the spinal cord, abnormal dendritic/spinous synaptic reconstructions and inflammation to improve NP. EA modulates three main types of P2X receptors: the P2X3 receptors located in sensory neurons themselves, the P2X4 receptors located in microglia, and the P2X7 receptors located in glial cells (microglia, astrocytes, and oligodendrocytes) ( 73 ).…”
Section: Mechanism Of Action Of Acupuncture In the Treatment Of Neuro...mentioning
confidence: 99%
“…Its blockage has been shown to alleviate neuropathic pain [132]. Furthermore, P2X7 agonists were shown to reduce electroacupuncture-related neuropathic pain-alleviating effects, as well as enhance morphological changes in the neurons of the spinal dorsal horn [133].…”
Section: Central Sensitization the Spinal Dorsal Horn Pain Processing...mentioning
confidence: 99%